Predictive Role of Anti-Mullerian Hormone in Spontaneous Miscarriage among Iraqi Pregnant Women - Naji, Zainab Abdul Wahed (American Journal of Biology and Natural Sciences, 2025)
Background: Early pregnancy loss, particularly during the first trimester, is a common reproductive complication with multifactorial causes. Anti-Müllerian Hormone (AMH), a marker of ovarian reserve, has recently been investigated for its potential role in predicting pregnancy outcomes. This study aims to evaluate the predictive role of serum AMH levels in first-trimester miscarriage among pregnant women in Iraq. Methods: This study was involving 129 pregnant women aged 20 to 40 years at ≤12 weeks of gestation. The case group included 79 women who experienced spontaneous miscarriage, while the control group consisted of 50 women with ongoing viable pregnancies, matched for age and gestational age. Serum AMH levels were measured and compared between the two groups. Maternal age and body mass index (BMI) were also assessed. Results: There was no significant difference in maternal age between the groups (p = 0.7316). However, BMI was significantly higher in the miscarriage group compared to the control group (p = 0.024). Serum AMH levels were significantly lower in the miscarriage group (1.653 ± 1.12 ng/mL) compared to the control group (2.682 ± 1.40 ng/mL), with a p-value < 0.05. Conclusion: Lower serum AMH levels are significantly associated with early pregnancy loss and may serve as a useful biomarker for identifying women at increased risk of miscarriage. Incorporating AMH testing into early pregnancy evaluation may improve reproductive care and risk stratification, particularly in resource-limited settings such as Iraq.